THE INFLUENCE OF INFORMATION TECHNOLOGY AND DIGITAL LITERACY ON USERS OF STUDENT SERVICES BASED ON THE SEPADU APPLICATION, RAJA ALI HAJI MARITIME UNIVERSITY: Pengaruh Teknologi Informasi Dan Literasi Digital Terhadap Pengguna Layanan Mahasiswa Berbasis Aplikasi SEPADUUniversitas Maritim Raja Ali Haji - Jumaiza farida; Edy Akhyary; Okparizan (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The development of information technology and digital literacy has brought a significant transformation in application-based services in higher education. This study analyzes the influence of information technology and digital literacy on the use of SEPADU application-based academic services at Raja Ali Haji Maritime University. With a quantitative approach where data was collected through a questionnaire distributed to 97 student respondents of Raja ALI Haji Maritime University. The results of the study found that digital literacy has a significant effect on the use of the SEPADU application, while information technology does not show a significant influence on the administrative services of SEPADU application users. The value of the correlation coefficient was 40.9% while the remaining 59.1% was influenced by other variables that were not studied in this study. The need to increase students' digital literacy and strengthen information technology infrastructure at UMRAH to support the optimization of campus digital services.